EFL STUDENTS' CHALLENGES IN SCRATCH-BASED COLLABORATIVE WRITING: A DESCRIPTIVE SURVEY STUDY - Rahma Amelia Putri; Rosi Anjarwati; Tatik Irawati; Ika Lusi Kristanti (Universitas Negeri Surabaya, 2026)
The use of digital learning tools has provided new opportunities to support collaborative writing in the English as a Foreign Language (EFL) classroom. Scratch is one of the digital learning platforms that can be utilized to support collaborative writing activities through its multimedia and storytelling features; however, students may experience various challenges during its implementation. Therefore, this study aimed to investigate EFL students' challenges in using Scratch as a digital learning tool for collaborative writing. This study employed a quantitative descriptive survey design involving 54 eleventh-grade students at SMA Negeri Jogoroto, Jombang, who had experience using Scratch in collaborative writing activities. Data were collected through a 20-item closed-ended questionnaire using a five-point Likert scale and analyzed using descriptive statistics, including mean scores and standard deviations, which were subsequently categorized according to a predetermined mean-interval classification. The findings showed that students experienced challenges categorized as high across all three dimensions examined. Digital Literacy Levels of Students was the most prominent challenge (M = 3.62), followed by Limited Access to Technological Infrastructure and Resources (M = 3.53) and Technical Issues and Compatibility Problems (M = 3.50). These findings indicate that students still faced difficulties with digital skills, technological resources, internet access, software compatibility, and technical support when using Scratch. In conclusion, the successful integration of Scratch in collaborative writing requires adequate digital literacy, reliable technological infrastructure, and continuous technical support. Therefore, English teachers and schools should provide sufficient training, improve technological facilities, and strengthen technical assistance to optimize the implementation of Scratch in EFL collaborative writing activities.